Quakes, eruptions, and other geologic cataclysms - Erickson, Jon, 1948- (New York : Facts on File, 1994)
Explores the varied processes behind (or beneath) all of the major geologic hazards, from earthquakes and volcanoes to floods and landslides; from dust storms and glaciation to meteor showers and mass extinctions.
The dynamic earth -- Earthquakes -- Volcanic eruptions -- Earth movements -- Catastrophic collapse -- Floods -- Dust storms -- Glaciers -- Impact cratering -- Mass extinctions.
Includes bibliographical references (p. 179-185), glossary, and index.
School Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Adult.
Young Adult
Keywords: Natural disasters; Natural disasters